PERAN KOPERASI SIMPAN PINJAM ROHUL LESTARI DALAM MENINGKATKAN KESEJAHTERAAN EKONOMI MASYARAKAT (Studi KSP Rohul Lestari Dusun Simpang. D Rambah Hilir-Rokan Hulu) - -, Mardiatun; Rahman, Arrafiqur; -, Afrizal (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2015)
Cooperative is a business unit engaged in economic and social basically have the same goal of helping boost economic growth which is the main goal of economic development. Research samples of 40 people. Daily merchandise respondents are 13 people or 32.5%. Rubber plantations are 9 people or 22.5%. Palm plantation 11 people or 27.5%. Agricultural businesses are 2 or 5%. Farm business 5 people or 12.5%. In analyzing the study data using qualitative descriptive method, only describes the results of the field when the interview questions. With the number of respondents 11 people who claimed the existence of cooperatives have as much impact on the welfare of 27.5% or 11 people borrower has oil palm plantations. While the impact of economic decline household income is a rubber plantation with respondents 9 people or 922.5%.